(untitled) (Nigerian Journal of Technology, 2018)
In ambient intelligence home networks, attacks can be on the home devices or the communication channel. This paper focuses on the channel attacks prevention by proposing Real Time Dynamic Source Routing (RTDSR) protocol. The protocol adopted the observation based cooperation enforcement in ad hoc networks (oceans) and collaborative reputation mechanism built on Dynamic Source Routing (DSR) protocol. The RTDSR introduced lookup table on the source, destination and intermediate nodes. It also ensures that data path with high reputation are used for data routing and a monitoring watchdog was introduced to ensure that the next node forward the packet properly. The RTDSR protocol was simulated and benchmarked with DSR protocol considering network throughput, average delay, routing overhead and response time as performance metrics. Simulation result revealed a better performance of RTDSR protocol over existing DSR protocol. http://dx.doi.org/10.4314/njt.v37i2.28